2014
DOI: 10.1002/adma.201400172
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Flexible Graphene Triboelectric Nanogenerators

Abstract: Transparent flexible graphene triboelectric nanogenerators as new promising applications of chemical vapor deposition‐grown graphene are successfully demonstrated. The work function and friction are decisive factors to understand the difference in output performance depending on the number of layers of graphene. In this work, we were able to power an LCD, LEDs, and an EL display using the electrical power output of the graphene triboelectric nanogenerator without any external energy source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
264
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(271 citation statements)
references
References 47 publications
(60 reference statements)
3
264
3
1
Order By: Relevance
“…Complicated tactile sensing system under bland skin is illustrated in Figure 15 . At present, pressure sensors are primarily based on the strength induced variation in capacitance,149, 150 piezoelectricity,151, 152 resistivity,17 triboelectricity 153. And graphene has been applied in the design of light and wearable pressure sensors.…”
Section: The Human‐like Senses and Feedbacksmentioning
confidence: 99%
“…Complicated tactile sensing system under bland skin is illustrated in Figure 15 . At present, pressure sensors are primarily based on the strength induced variation in capacitance,149, 150 piezoelectricity,151, 152 resistivity,17 triboelectricity 153. And graphene has been applied in the design of light and wearable pressure sensors.…”
Section: The Human‐like Senses and Feedbacksmentioning
confidence: 99%
“…A vast amount of advanced materials would be good choices, such as graphene, 38,39 carbon nanotube, 40 and nano-Ag ink. 41 It is found that nanoscale roughness on graphene can increase the surface charges, which can improve the output power of the TENG.…”
Section: Prospects and Challengesmentioning
confidence: 99%
“…In the last 5 years, a significant amount of research work has been achieved to improve the performance and application of flexible TENGs. [14][15][16] This review focuses on the progress of TENGs as flexible power sources for flexible electronics, which contain both scientific understanding and technology developments. First, we present a summary of the basic principle of TENGs, including fundamentals, structural designs, work mechanism, and output performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, transparent TENGs using indium tin oxide (ITO) or graphene as electrodes have been achieved, which enable applications that require high transparency such as touch screens [31][32][33][34][35] . Our previous work shows that using C 4 F 8 to treat uncured PDMS could deposit fluorocarbon polymer and a wrinkle structure in single step [18][19][20] , which had the advantage of significantly increasing the performance of the flexible TENG.…”
Section: Introductionmentioning
confidence: 99%